The haunted castle - Stilton, Geronimo; Cernuschi, Claudio Grassini, Valentina Heim, Julia (Scholastic New York, 2011)
Uncle Samuel S. Stingysnout invites the whole Stilton family to creepy, faraway Penny Pincher Castle for a big surprise